ULTRASONIC TOMOGRAPHY ANISOTROPY ANALYSIS OF SDW- 5ST1 CORES IN RESERVOIR CHARACTERIZATION FOR SADEWA FIELD, KUTAI BASIN, EAST KALIMANTAN - Nurhazlita, Rahma
The SDW-5ST1 well is one of the cored wells of the Sadewa Field, one of the fields that will be developed. To determine the effect of anisotropy on the reservoir rock, the anisotropy of the core rock structure was measured using ultrasonic tomography where this tomography can give a smaller image than seismic tomography. Data on the anisotropy level of rock core samples was obtained by measuring the travel time of P and S waves with ultrasonic tomography method. Measurements were made at various angles based on the Vertically Transverse Isotropic (VTI) model. After the anisotropy data parameters of rock core samples were obtained, an analysis of the relationship between the anisotropy parameters and the physical and elastic properties of each sample was carried out. Data from ultrasonic tomography measurements were also processed using the MSIRT algorithm to produce data in the form of elastic properties of rock core samples. After the anisotropy data parameters of the rock core samples were obtained, an analysis of the relationship between the anisotropy parameters and the elastic properties, physical properties, and petrographic descriptions of each sample was carried out. The core sample of SDW-5ST1 is sandstone from upper Miocene reservoir rock with upper slope fan facies and deposited in a lowstand tract system. The results of the evaluation of the upscaling factor showed that there was not a good enough correlation between the well log data and the bataun core data in the upper slope fan facies. Based on the influence of rock properties on anisotropy, for SDW-ST1 sandstone core, anisotropy is influenced by layer structure, % clay, intergranular porosity, porosity, permeability, acoustic impedance, Vp/Vs, shear modulus, bulk modulus, Young's modulus, Poisson's ratio, and the lame constant.